Sistem Kontrol dan Monitoring Pemberi Pakan Ikan Otomatis Berbasis IOT - Safitri Safitri; Dian Megah Sari; Chairi Nur Insani; Sitti Aulia Rachmini (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2022)
The activity of keeping ornamental fish using an aquarium is still very popular with fans. An important factor in maintaining ornamental fish in an aquarium is the timing of feeding the fish. Therefore the author aims to create an Internet of Things-based automatic fish feeder control and monitoring system. The type of research used is a combined research (mix method) using blackbox testing, the results of this study are a prototype system where when The RTC is set according to the fish's feeding demand schedule, the Nodemcu commands the servo motor to open the fish's feeding valve, and the ultrasonic sensor detects the remaining food in the storage tank. The received sensor reading data will be sent to Telegram as an information display media.Furthermore, the data used was 5 trials with an average of 1 gram of feedissued.